Storage and Sequestration of Carbon by Leguminous and Non-leguminous Trees on Red Lateritic Soil of Chhattisgarh - Dhruw, S. K.; Singh, Lalji; Singh, A. K. (Indian Forester, 2009)
In the present study, the storage and sequestration of carbon is described for leguminous trees (Cassia siamia, Dalbergia sissoo) vs. non-leguminous tree (Tectona grandis Linn. f.) in red lateritic soil of Chhattisgarh. Carbon concentrations of different components of eight year old trees were found to be 39.3-42.55 per cent, 41.06-43.3 per cent and 40.74-46.5 per cent, 44.4- 45.3 per cent in leaves, branches, stems and roots respectively. Total storage of carbon ranged from 1,354.7 to 3,079.86 kg ha-1. Out of the total stored carbon, 70 per cent were estimated to be in above ground parts while 30 percent in below ground parts. Storage of carbon was greater in leguminous trees. Similarly, carbon sequestration was also higher by leguminous trees compared to that of non-leguminous trees. Rate of carbon sequestration was a substantial i.e. 31 per cent for below ground root the same for above ground components was 69 per cent. Study reveals the potential of leguminous trees in storage and sequestration of carbon in red lateritic soil and has implications for restoration of degraded land.